Assessing Institutional Betrayal Among Female Veterans Who Experienced Military Sexual Trauma: A Rasch Analysis of the Institutional Betrayal Questionnaire.2. Issue 23 (December 2021) - Monteith, Lindsey L.; Schneider, Alexandra L.; Holliday, Ryan; Bahraini, Nazanin H.
Military sexual trauma (MST; i.e., sexual harassment and/or sexual assault during one's military service) is highly prevalent among female veterans and is associated with numerous adverse health and psychosocial sequelae. When institutions fail to prevent sexual trauma from happening or respond in an unsupportive manner (i.e., institutional betrayal [IB]), MST survivors typically report more severe health-related outcomes. Although the Institutional Betrayal Questionnaire.2 (IBQ.2) was developed to assess IB, no studies have examined the factor structure or dimensionality of the IBQ.2 among MST survivors. In addition, initial research has reported differing factor structures for this measure. The present study examined the dimensionality and factor structure of the IBQ.2, and tested for differential item functioning (DIF) based on whether military sexual assault was experienced. The sample comprised 235 female veterans who reported a history of MST in an anonymous national survey. Rasch analysis suggested multidimensionality and DIF based on history of military sexual assault. Exploratory factor analysis and parallel analysis suggested the IBQ.2 comprises three factors: (1) Environment Leading to MST, (2) Institutional Response to MST, and (3) Institutional Belongingness following MST. Although these results suggest that the IBQ.2 is multidimensional, the three-factor model had significant issues with respect to dimensionality, item fit, and person separation and reliability. Thus, using the full IBQ.2 may be more advantageous. Further examination of the IBQ.2 is warranted to ensure optimal assessment of IB in relation to MST, irrespective of whether the MST comprised sexual harassment or sexual assault, as well as to ensure that the IBQ.2 is culturally meaningful for MST survivors.